PERCEIVED RISK, TRUST AND PURCHASE INTENTION IN ONLINE MARKETPLACE: PERSPECVICE OF CONSUMERS IN MANADO, INDONESIA - Kindangen, Devina A.; Karamoy, Herman; Saerang, Regina T. (Universitas Sam Ratulangi, 2021)
Previous studies indicated that perceived risk and trust have a significant impact towards consumer online buying behavior. This research focuses and aims to analyze how trust mediates perceived risk and consumer buying intention in online marketplaces. The study is limited in e-marketplace users in Manado, Indonesia. This study uses quantitative approach and utilized PLS-SEM as the tool of analysis. The number of samples are 97 respondents. Results shows that perceived risk has negative significant impact on e-marketplace consumer trust; there is no direct impact from perceived risk toward purchasing intention; there is a significant impact from trust toward purchasing intention; and trust mediates their perceived risk of the e-marketplace toward their purchase intention. The result of this study advises business managers to consider trust as the most crucial factor in minimizing risk perception and improving consumers’ intention to purchase in online platform. Keywords: trust, perceived risk, purchase intention, e-marketplace